Overvekt hos gravide - en utfordring i svangerskapsomsorgen - Wenke Moldjord; Sevald Høye; Kari Kvigne (Septentrio Academic Publishing, 2015)
The purpose of this study is to gain knowledge about the challenges midwives and public nurses are experiencing in health prevention and health promotion to obese pregnant women, and their reflections regarding the need for change in practice. Method: The study has a qualitative exploratory design. Data was created by multistage focus group interviews and analyzed inspired by Lundman and Granheim's content analysis. The focus groups consisted of midwives and public health nurses. Results: The informants were aware that obesity in pregnancy may cause complications for both mother and child, but they experienced obesity and lifestyle changes as challenging in antenatal care. Weight and body were perceived as something vulnerable. Informants found it hard to talk about weight because they were afraid of reactions from the pregnant women. They also expressed insecurity regarding their own expertise when it comes to communication and nutrition. Informants expressed the need for more interdisciplinary cooperation between different health workers in community health. They experienced such cooperation difficult to achieve.